L‐dopa increases α‐synuclein DNA methylation in Parkinson's disease patients in vivo and in vitro. Issue 13 (14th July 2015) - Schmitt, Ina; Kaut, Oliver; Khazneh, Hassan; deBoni, Laura; Ahmad, Ashar; Berg, Daniela; Klein, Christine; Fröhlich, Holger; Wüllner, Ullrich
Abstract: Background: Increasing gene dosages of α‐synuclein induce familial Parkinson's disease (PD); thus, the hypothesis has been put forward that regulation of gene expression, in particular altered α‐synuclein gene methylation, might be associated with sporadic PD and could be used as a biological marker. Methods: We performed a thorough analysis of α‐synuclein methylation in bisulfite‐treated DNA from peripheral blood of 490 sporadic PD patients and 485 healthy controls and in addition analyzed the effect of levodopa (l ‐dopa) on α‐synuclein methylation and expression in cultured mononuclear cells. Results: α‐Synuclein was hypomethylated in sporadic PD patients, correlated with sex, age, and a polymorphism in the analyzed sequence stretch (rs3756063). α‐Synuclein methylation separated healthy individuals from sporadic PD with a specificity of 74% (male) and 78% (female), respectively. α‐Synuclein methylation was increased in sporadic PD patients with higherl ‐dopa dosage, andl ‐dopa specifically induced methylation of α‐synuclein intron 1 in cultured mononuclear cells. Conclusions: α‐Synuclein methylation levels depended on disease status, sex, age, and the genotype of rs3756063. The pharmacological action ofl ‐dopa was not limited to the dopamine precursor function but included epigenetic off‐target effects. The hypomethylation of α‐synuclein in sporadic PD patients' blood already observed in previous studies was probably underestimated because of effect ofl ‐dopa, which was not known previously. The analysis of α‐synuclein methylation can help to identify nonparkinsonian individuals with reasonable specificity, which offers a valuable tool for researchers and clinicians. © 2015 International Parkinson and Movement Disorder Society